O sonetizmu Leopolda Staffa - Štefan, Rozka (Slavistična revija, 1997)
The paper deals with the production of Leopold Staff, which is based on the classical (Mickiewicz's) sonnet pattern, and with deviation from this pattern, i.e., with respect to its versification as well as to its cyclic character.
Keywords: literarne študije; Lithuanian Metrica; metrika; Polish literature; poljska književnost; poljska poezija; soneti; Staff, Leopold, 1878-1957